Hepatic arterial infusion chemotherapy with implantable arterial access port for advanced-stage hepatocellular carcinoma: a case report - Jiang, Xin; Aljbri, Afaf; Liu, Jiaxuan; Shang, Liqi; Tian, Yulong; Shao, Haibo (Frontiers in Oncology, 2024)
Background: Hepatocellular carcinoma (HCC) is a common gastrointestinal malignancy characterized by high incidence rates and a poor prognosis. Common treatment modalities include surgery, ablation, and transarterial chemoembolization (TACE). Hepatic arterial infusion chemotherapy (HAIC) has long been used in the treatment of unresectable liver cancer. In recent years, the combination of anti-angiogenesis therapy and immune checkpoint inhibitors has shown significant advances in the treatment of middle-and advanced-stage liver cancer. This report presents a case of HCC in which sustained benefits are achieved through a combination of HAIC of infusional oxaliplatin, leucovorin, and fluorouracil (FOLFOX), targeted therapy, and immunotherapy.Main Body: A 64-year-old male patient was diagnosed with a parenchymal mass in the liver by a three-dimensional color ultrasound one month before admission, prompting consideration of liver cancer. Subsequently, computed tomography (CT) imaging performed at our hospital identified mass shadows in the right lobe of the liver and diffuse nodules throughout the liver, suggesting malignant lesions. Upon admission, the patient presented poor general health and baseline indicators. Following symptomatic treatment, the patient underwent a therapeutic regimen that combined transarterial infusion port FOLFOX-HAIC with Lenvatinib and Sintilimab. This combined treatment resulted in significant liver tumor necrosis and effectively managed the patient's condition.The combined approach of using FOLFO-HAIC transarterial infusion alongside anti-angiogenesis therapy and immune checkpoint inhibitors has shown promising results that provide substantial benefits. This combined regimen has demonstrated the potential to improve treatment compliance among certain patients. Given these encouraging outcomes, further investigation into this combination therapy regimen is warranted to understand better its efficacy and potential broader applications in clinical settings.